Perbedaan Kadar Kreatinin Pada Serum Lipemik Yang Diolah Dengan Polyethylene Glycol 6000 8% Dan High Speed Sentrifugasi - Wheny Mufita Sari; Ni Ratih Hardisari; Sujono Sujono (POLTEKKES KEMENKES YOGYAKARTA, 2017)
Lipemic serum is a turbid serum caused by enhancement of lipoprotein consentration mainly chylomicron and very low density lipoprotein (VLDL). It can cause interference of physics and chemistry, spectrofotometri, not homogen sample and volume displacement effect that make the result of the laboratory test inacurate, including creatinin test. The method that can be used to clear up lipid on the lipemic serum is centrifugation, extraction with polar solvent, dilution, and precipitation with Polyethylene Glycol 6000 8%. The aim of the study is to know creatinine level defference of lipemic serum using Polyethylene Glycol 6000 8% in creatinine test. This research was a true experiment with Pretest Postest Control Group Design. This research was conducted in October – November 2016 at Pathology Clinic of Panembahan Senopati Hospital, Bantul. The result of creatinine scores before treatments was 0,98 mg/dL, after being added with Polyethylene Glycol 6000 8% it became 0,98 mg/dL, and after being processed using High Speed Centrifugation, it was 1,11 mg/dL. The result of statistic test using Independent Sample T-Test obtained the Asymp sig value of 0,003 (p<0,05) which means there is no difference of creatinine scores in lipemic serum processed by adding Polyethylene Glycol 6000 8% and High Speed Centrifugation.